Mindfulness dan Collaboration Networking dalam Meningkatkan Resiliensi Industri Pariwisata Jawa Tengah Selama Pandemi - Pratiwi, Ratih; Satatoe, Y R (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2022)
This research aimed to analyze the factors that caused a performance decline on reservation employees back in 2021 and formulate appropriate strategies to improve reservation employee performance at Hotel XYZ. This study used a qualitative approach and research data obtained through interviews, observations, and documentation studies. The results showed that reservation employees at Hotel XYZ experienced a performance decline because of the following: 1). decreased work motivation, 2). awards that were not fully obtained as a form of appreciation from the organization and leader, and 3). the leadership role of the Director of Revenue and Reservation, who had not been effective because it was not by the nature and personality of the employees. Based on the research results, several things could be done to improve the performance of reservation employees. The organization is expected to provide employees with full basic salary and overtime wages and bring back family gatherings. Leaders are expected to give praise for employee achievements and boost employee confidence. Keywords: Employee Performance, Strategic Formulation, Reservation